2020
DOI: 10.3724/sp.j.1006.2020.94111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous melatonin on physiology and yield of soybean during seed filling stage under drought stress

Abstract: Drought stress reduces soybean yield. Exploring the mechanism of improving drought tolerance and reducing yield loss is of great significance for soybean production. Melatonin application can alleviate the growth inhibition and oxidative damage of plants under drought stress. In this experiment, the effects of foliar application of melatonin on photosynthesis, stress resistance, carbon and nitrogen metabolism and yield of soybean during seed filling stage under drought stress were studied in 2017-2018. The app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…However, the root system of soybeans is underdeveloped, while water demand during the plant life cycle is high. Indeed, the root system is more sensitive to adverse conditions, such as drought, which may cause yield losses ranging from 25 to 50% (Zou et al, 2020). Furthermore, the soybean plant is most sensitive to water deficit during the flowering period, when water shortage will most seriously affect yield.…”
Section: Introductionmentioning
confidence: 99%
“…However, the root system of soybeans is underdeveloped, while water demand during the plant life cycle is high. Indeed, the root system is more sensitive to adverse conditions, such as drought, which may cause yield losses ranging from 25 to 50% (Zou et al, 2020). Furthermore, the soybean plant is most sensitive to water deficit during the flowering period, when water shortage will most seriously affect yield.…”
Section: Introductionmentioning
confidence: 99%
“…Drought, one of the typical abiotic stresses, is the most important factor affecting the crop yield and quality [ 6 ]. Zou et al [ 7 ] found that the yield loss of soybean caused by drought could reach 25–50%. According to the occurrence of drought and the degree of impact, with reference to “Grade of agricultural drought” [ 8 ], the water potential is an important basis for judging the level of drought.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, melatonin has been widely used as a protective agent against multiple stresses including unfavourable salt concentrations, ultraviolet radiation, toxic chemicals, extreme temperature, osmotic stress, pathogen infection, and nutritional defects (Zhang et al 2017a;Fan et al 2018;Bawa et al 2020;Mohamed et al 2020;Zhang et al 2020). Under abiotic stress including drought, the alleviation effect of melatonin on plant growth may also be attributed to its regulation of carbon and nitrogen metabolism (Cao et al 2019;Zou et al 2020). Some studies have pointed out that melatonin could play a role in plants by enhancing cell division, promoting photosynthesis and carbohydrate synthesis, and other carbon metabolic pathways (Wei et al 2015).…”
Section: Introductionmentioning
confidence: 99%